Studies on the physico-chemical properties and fatty acid composition of Nyctanthes arbor-tristis Linn leaves - Rahman, Mohammad Mizanur; Roy, Sudhangshu Kumar; Shahjahan, Mohammad (Journal of the Bangladesh Chemical Society, 2012)
Seven fatty acids were isolated from pet-ether extract of Nyctanthes arbor-tristis Linn (Seuli) leaves. The relative percentages of the major fatty acids were identified by GLC as palmitic acid (23.88%), linoleic acid (8.95%), stearic acid (47.56%) and oleic acid (5.07%). The yield of the leaves fat was 2.10%. Acid value of seed oil was found to be 76.27 and suggests that this oil is inedible. Physico-chemical characteristic, such as acid value, iodine value, moisture, ash, lignin, crude fibre, fat, protein and carbohydrate of the Seuli leaf were also determined. Keywords: Seuli leaves; Nyctanthes arbor-tristis Linn; fatty acids composition. DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9711 Journal of Bangladesh Chemical Society, Vol. 24(2), 215-220, 2011